2018
DOI: 10.1053/j.gastro.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Proton Density Fat Fraction Associates With Progression of Fibrosis in Patients With Nonalcoholic Fatty Liver Disease

Abstract: Markers are needed to predict progression of nonalcoholic fatty liver disease (NAFLD). The proton density fat fraction, measured by magnetic resonance imaging (MRI-PDFF), provides an accurate, validated marker of hepatic steatosis; however, it is not clear whether the PDFF identifies patients at risk for NAFLD progression. We performed a follow-up study of 95 well-characterized patients with biopsy-proven NAFLD and examined the association between liver fat content and fibrosis progression. MRI-PDFF measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 26 publications
2
88
0
Order By: Relevance
“…MRI‐PDFF measurement correlates with histologically determined steatosis both in cross‐sectional and in prospective evaluation . In keeping with a causal role of hepatic fat in determining liver disease progression, high MRI‐PDFF has now been associated with liver fibrosis progression, independently of several metabolic confounders . This evidence makes evaluation of MRI‐PDFF an attractive option for non‐invasive yet accurate quantification of hepatic fat content in early‐stage NAFLD trials evaluating treatments that modulate fat accumulation .…”
Section: Imaging Studiesmentioning
confidence: 75%
See 2 more Smart Citations
“…MRI‐PDFF measurement correlates with histologically determined steatosis both in cross‐sectional and in prospective evaluation . In keeping with a causal role of hepatic fat in determining liver disease progression, high MRI‐PDFF has now been associated with liver fibrosis progression, independently of several metabolic confounders . This evidence makes evaluation of MRI‐PDFF an attractive option for non‐invasive yet accurate quantification of hepatic fat content in early‐stage NAFLD trials evaluating treatments that modulate fat accumulation .…”
Section: Imaging Studiesmentioning
confidence: 75%
“…16,17 On the other hand, accurately quantified hepatic fat has now been linked with liver fibrosis progression. 18,19 Although fibrogenesis may self-perpetuate independently of hepatic fat and inflammation after a wound healing response has been initiated, in patients with NAFLD without advanced disease amelioration of the metabolic profile and hepatic fat as a consequence of lifestyle modifications or bariatric surgery has been associated with resolution of NASH and improvement in fibrosis in those with more marked weight loss. 20,21 Therefore, evaluation of fibrosis associated with hepatic fat accumulation ("steatofibrosis") may represent a simpler marker of disease evolution in clinical practice and therapeutic trials.…”
Section: Natur Al His Torymentioning
confidence: 99%
See 1 more Smart Citation
“…This was a cross-sectional analysis of a discovery cohort that included 156 participants prospectively recruited between October 2011 and May 2014 at the University of California at San Diego (UCSD) NAFLD Research Center. [22][23][24][25] All patients with suspected NAFLD with a clinical indication for liver biopsy underwent a careful evaluation for other causes of hepatic steatosis and liver disease through a standardised research visit including detailed medical and alcohol use history as well as anthropometric and physical examination. The study was performed according to STARD criteria listed in online supplementary table 1.…”
Section: Materials and Methods Study Participants And Design Of The Bmentioning
confidence: 99%
“…It included patients with MRIPDFF ≥15% which would have allowed us to see a significant difference relative to placebo thereby reducing the likelihood of type 2 error. Indeed, it was recently shown that patients with higher liver fat (MRIPDFF ≥15.7%) have higher fibrosis progression . Thus, these trial participants were more likely to have progressive NAFLD and were appropriate candidates for an early phase trial.…”
mentioning
confidence: 99%